Modification of metal-cutting plates from tungsten-free hard alloy grade KNT16 by continuous ion beams - A. M. Badamshin; S. N. Povoroznuyk; V. V. Akimov; E. A. Rogachev; A. A. Krutko (Омский научный вестник)
This work is devoted to the problem of developing technological operations aimed at improving the structure and properties and, as a result expanding the scope of metalcutting inserts from tungsten-free hard alloys. The search for alternative analogues of traditional tungsten-cobalt hard alloys is an urgent task of modern materials science, due to the high cost and shortage of their components. In this paper, we study the effect of a continius ion beam on the change in the morphology, mechanical properties, and performance characteristics of metal-cutting inserts made of tungsten-free hard alloy grade KNT16 (TiCN-NiMo). It has been found that the effect of continuous ion beams leads to a significant change in the wear resistance of cutting plates during turning operations on mediumcarbon steel 40KhN. A rational composition of the ion beam has been established, in which the cutting plate is subjected to the least wear after completion of the test cycle. Using the methods of scanning electron microscopy and scanning probe microscopy, a study of the microrelief and morphology of the surface of the samples is carried out.